STRATEGY OF INFORMATION IMPLEMENTATION METHODOLOGY TECHNOLOGIES IN THE LEARNING PROCESS (Pedagogy of Higher and Secondary Education, 2010)
In this article ways of readiness of the future teachers to use of competition technologies in education process are considered.
Keywords: information technologists; independently; model utilization information machines; cognitive component; competition